Pentingnya Pendidikan Kewarganegaraan dalam Mengatasi Krisis Moral di Era Milenial Mahasiswa Farmasi Universitas PGRI Adi Buana - Nurul Humaina; Marsha Driz Calillah; Sofia Sofia; Jamiatul Hasanah; Ahla Cholisatun; Suci Nurjanah; Nadhifa Salsabila Putri; Leili Sasmita; Dinda Ayu Pratsila; Farda Wali Waufa; Maria Margareta; Chika Aulia Putri; Suyono Suyono (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The moral crisis that is currently hitting the millennium era has raised deep concerns about the moral values of today's society. The ethical crisis in the millennial era is becoming an increasingly deep and complex problem. Various factors, such as the influence of globalization, technological progress, and social change, have shaped the context of individual behavior and weakened basic moral values. In this context, this review examines the importance of citizenship education as the main solution for forming individual character and social ethics in the  millennium era. This study discusses the concept of citizenship education, the role of educational institutions and the challenges faced in realizing civic values in education. The research results highlight the importance of citizenship education in overcoming the current moral crisis and emphasize the need for cooperation between government, educational institutions and society to achieve this goal.